2018
DOI: 10.1093/occmed/kqy085
|View full text |Cite
|
Sign up to set email alerts
|

Vascular component of hand-arm vibration syndrome: a 22-year follow-up study

Abstract: BackgroundVibration-induced white finger (VWF) is often assessed using the Stockholm Workshop Scale (SWS) and cold challenge plethysmography. However, long-term longitudinal studies using both methods are scarce.AimsTo study the long-term course and prognostic factors of VWF assessed with the SWS and photoplethysmography (PPG), and to examine the effects of lifestyle on PPG score, regardless of VWF status.MethodsForty male construction workers were examined with a test battery and clinical examination in 1994 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
1
10
0
1
Order By: Relevance
“…Our cross‐sectional study design limits our ability to draw firm conclusions about causality, since exposures and outcomes were measured at the same time. However, associations between our study's work exposures and health outcomes have been shown to be causally related in prospective studies 15,38–40 …”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Our cross‐sectional study design limits our ability to draw firm conclusions about causality, since exposures and outcomes were measured at the same time. However, associations between our study's work exposures and health outcomes have been shown to be causally related in prospective studies 15,38–40 …”
Section: Discussionmentioning
confidence: 75%
“…However, associations between our study's work exposures and health outcomes have been shown to be causally related in prospective studies. 15,[38][39][40] Self-report of exposures and outcomes increases the possibility of information bias. For example, it was suggested that some (Table 2), due to missing covariate, exposure and health data, only between 2334 and 2787 participants were included in each of these regression analyses.…”
Section: Study Limitationsmentioning
confidence: 99%
“…In 1994, all employees ( n = 211) in two workshop units (sheet metal workers performing grinding/welding and machinists) of an engineering and construction company participated in a HAVS examination [4]. We used the 1994 questionnaire to select workers for the 2017 study.…”
Section: Methodsmentioning
confidence: 99%
“…The vibration measurements are described in the ISO 1309-1/2 standard. Blood samples (cotinine, carbohydrate-deficient transferrin (CDT), glycosylated haemoglobin (HbA1c) and folate) were collected during the examination in 2017, as described previously [4].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation